Ouch! moments : when words are used in hurtful ways - Genhart, Michael; e (Washington, DC : Magination Press, 2016)
The reader is encouraged to be caring and to take a stand when someone uses hurtful words.
"American Psychological Association."
Keywords: Conduct of life -- Fiction; Caring -- Fiction; Caring -- Fiction; Fiction